VISUALISASI STRUKTUR KRISTAL KERAMIK PEROVSKITE MENGGUNAKAN VESTA - Sundami Restiana; Ari Sulistyo Rini (Universitas Riau, 2018)
Visualization of crystal structures and simulation of X-ray diffraction patterns of perovskite ceramic was successfully performed by VESTA software programs. The purpose of this research is to obtain the relation of lattice parameter, and composition to the diffraction pattern. The software program produces crystal structure information and a representative X-ray diffraction pattern for the ceramic materials. The program needs several input parameters such as the coordinates of each constituent atom, lattice parameters, and space symmetry. The obtained output of the software program are in the form of diffraction pattern graph and crystal structure data which gives the description of the profile and type (phase) of ceramic material. The results showed that the peak position and intensity of the diffraction pattern are influenced by the arrangement of the atoms within the unit cell. The addition of impurity atoms such as Sr on the Ba side in BaTiO3 causes the BaTiO3 structure changes from Orthorombic (a≠b≠c) to Tetragonal (a=b≠c) structure. Based on the simulation, it can be predicted that the critical concentration of the change of structure occur at Sr concentration about 0.4.